Energy labeling and the economic viability in residences of the project my house my life - Vicente, Thales Tati Gonçalves; Gabriel, Elaise; Rigon, Ursula Maira Maciel; Leão, Marlon (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The significant increase in the electricity consumption over the past decades by the residential sector has stimulated the creation of initiatives which are aiming the energy efficiency (EE). In addition to laws that were enacted in order to increase EE, it was launched in 2012 the Quality Technical Regulation for Energy Efficiency Level of Residential Buildings (RTQ-R), which it sets parameters to be followed in the labeling of an Autonomous Housing Unit (UH). This research had as objective proposes alternatives to increase the energy efficiency level of a residential complex named My House My Life (Minha Casa Minha Vida - MCMV). Moreover, it was calculated the construction costs and evaluated the economic viability of the investment. Thus, it was evaluated the envelope and the water heating system through prescriptive method. The obtained results classified the current housing as D level and showed that a few changes are needed to reach the level A. Through thermal energy simulation it was determined by the new classification a reduction of 2/3 in electricity consumption. The increase in the construction costs to achieve the level A is lower than the cost savings over the building's lifetime. Currently, the Selic rate of 14.25% unfeasible the investment due to the opportunity cost, becoming feasible with the kWh cost higher than R$ 0.97 or with basic interest rates lower than 9.5%.